Are antihistamines an effective treatment for drug‐induced bone pain?. Issue 2 (February 2017) - Hresko, Heather; Kraus, Connie
Abstract : EVIDENCE‐BASED ANSWER : Loratadine, given concurrently with granulocyte‐colony stimulating factor (G‐CSF), does not prevent bone pain more than placebo (SOR: B, single RCT). Hydroxyzine or astemizole (no longer available) given before or concurrently with G‐CSF, are associated with less growth factor‐induced bone pain (SOR: C, prospective cohort study and case reports).